Zanthoxylum Species: A Review of Traditional Uses, Phytochemistry and Pharmacology in Relation to Cancer, Infectious Diseases and Sickle Cell Anemia - Okagu, Innocent Uzochukwu; Ndefo, Joseph Chinedum; Aham, Emmanuel Chigozie; Udenigwe, Chibuike. C. (Frontiers in Pharmacology, 2021)
The health benefits and toxicity of plant products are largely dependent on their secondary metabolite contents. These compounds are biosynthesized by plants as protection mechanisms against environmental factors and infectious agents. This review discusses the traditional uses, phytochemical constituents and health benefits of plant species in genus Zanthoxylum with a focus on cancer, microbial and parasitic infections, and sickle cell disease as reported in articles published from 1970 to 2021 in peer-reviewed journals and indexed in major scientific databases. Generally, Z. species are widely distributed in Asia, America and Africa, where they are used as food and for disease treatment. Several compounds belonging to alkaloids, flavonoids, terpenoids and lignans, among others have been isolated from Z. species. This review discusses the biological activities reported for the plant species and their phytochemicals, including anticancer, antibacterial, antifungal, antiviral, trypanosomal, antimalarial and anti-sickling properties. The safety profiles and suggestions for conservation of the Z. species were also discussed. Taken together, this review demonstrates that Z. species are rich in a wide range of bioactive phytochemicals with multiple health benefits, but more research is needed towards their practical application in the development of functional foods, nutraceuticals and lead compounds for new drugs.